Characteristics of human center of pressure shifts in forward-backward, left-right, and oblique directions in standing posture and their effect on mobile device manipulation - Masaharu KOMORI; Tatsuro TERAKAWA; Taichi INOUE; Mitsuki MORIMOTO (Mechanical Engineering Journal, 2025)
A candidate control method for next-generation standing-type omnidirectional personal mobility vehicles involves the user shifting their center of pressure (COP) to steer the vehicle. However, the characteristics of human COP shifts in the forward-backward, left-right, and oblique directions for mobile vehicle applications are not well understood. In this study, we investigated the accuracy of the COP shift direction and the effects of neck and hip rotation on the COP shift in the forward-backward, left-right, and oblique directions. The results show that the foot center of pressure direction almost exactly matched the target COP direction when the target COP shift was in the forward and left-right directions regardless of the rotation of the neck and hips. However, when the target COP direction was the oblique forward direction, the measured foot center of pressure direction was shifted to the left or right. With rotation of the neck and hips, when the target COP direction was backward, there was a difference between the target direction and the actual direction of foot COP movement. This difference was found to depend on the direction of neck and hip rotation (left or right). In addition, an experiment was conducted in which the user manipulated an object that could move in any direction in a virtual space by moving their COP. The results show that when the target COP direction was the oblique forward or backward direction, the object movement direction tended to shift left or right from the target direction at the start of movement, which is related to the accuracy of the COP movement.